1q21.1 Microduplication expression in adults - Dolcetti, Alessia (2012)
PURPOSE: Rare, recurrent chromosome 1q21.1 duplications have been associated with developmental delay, congenital anomalies, and macrocephaly in children. Data on adult clinical expression would help to inform genetic counseling. METHODS: A systematic review of 22 studies reporting 107 individuals (59 children and 48 adults) with 1q21.1 duplications was conducted. We compiled the available phenotypic data to attempt to identify the most highly associated clinical features and to determine expression in adults. We also report on seven adult cases newly identified in the studies of schizophrenia and tetralogy of Fallot at our center. RESULTS: Five cases were ascertained as controls, 32 as relatives of probands, and 70 as having clinical features: autism spectrum disorder (n = 15), congenital heart disease (n = 12), schizophrenia (n = 10), or other, mostly developmental, features (n = 33). The 1q21.1 duplication was significantly enriched in the cohorts with schizophrenia (P = 0.0155) and tetralogy of Fallot (P = 0.0040) at our center as compared with controls. There was a paucity of clinical data for adults; the most common features, other than those used for ascertainment, included macrocephaly and abnormalities of possible connective tissue origin (e.g., carpal tunnel syndrome). CONCLUSION: Further data are needed to characterize lifetime expression of 1q21.1 duplications. These initial results, however, suggest that anticipatory care should include attention to later-onset conditions such as schizophrenia.